Equilibrium Exchange Rates and Misalignments: The Case of Homogenous Emerging Countries - Christian K. Tipoy; Marthinus C. Breitenbach; Mulatu F. Zerihun (SPOUDAI - Journal of Economics and Business, 2016)
We compute the exchange rate misalignment for a set of emerging economies between 1980 and 2013 using the behavioural equilibrium exchange rate definition. The real equilibrium exchange rate is constructed using a parsimonious model and estimators that are robust to cross-sectional independence and small sample size bias. We find that these countries tend to intervene to avoid real appreciation of their currencies following a rise in relative productivity, casting doubt on the Balassa-Samuelson effect. East-Asian countries have maintained their currencies at an artificially low level in order to remain competitive and boost economic growth these past years.
Keywords: F31; C23; 330; equilibrium exchange rate; panel cointegration; autoregressive distributed lag